Example-Driven Procedural Urban Roads - Nishida, G.; Garcia-Dorado, I.; Aliaga, D. G. (Computer graphics forum, 2016)
Synthesizing and exploring large‐scale realistic urban road networks is beneficial to 3D content creation, traffic animation and urban planning. In this paper, we present an interactive tool that allows untrained users to design roads with complex realistic details and styles. Roads are generated by growing a geometric graph. During a sketching phase, the user specifies the target area and the examples. During a growing phase, two types of growth are effectively applied to generate roads in the target area; example‐based growth uses patches extracted from the source example to generate roads that preserve some interesting structures in the example road networks; procedural‐based growth uses the statistical information of the source example while effectively adapting the roads to the underlying terrain and the already generated roads. User‐specified warping, blending and interpolation operations are used at will to produce new road network designs that are inspired by the examples. Finally, our method computes city blocks, individual parcels and plausible building and tree geometries. We have used our approach to create road networks covering up to 200 km2 and containing over 3500 km of roads. Synthesizing and exploring large‐scale realistic urban road networks is beneficial to 3D content creation, traffic animation and urban planning. In this paper, we present an interactive tool that allows untrained users to design roads with complex realistic details and styles. Roads are generated by growing a geometric graph. During a sketching phase, the user specifies the target area and the examples. During a growing phase, two types of growth are effectively applied to generate roads in the target area; example‐based growth uses patches extracted from the source example to generate roads that preserve some interesting structures in the example road networks; procedural‐based growth uses the statistical information of the source example while effectively adapting the roads to the underlying terrain and the already generated roads.